GLACIAL LANDFORMS IN TIBET - A geomorphological study of the western Himalayas - Blomgren, Ida (2023)
Glacial landforms on the Tibetan Plateau and its surrounding areas have long been an object of interest and study in the geology community. The knowledge of their location and distribution may prove to be crucial for numerous future studies. This thesis aimed to map glacial landforms in an area on the Tibetan Plateau located at the intersection of India, Nepal and China, and investigate their distribution as well as make an educated guess at the previous location of past glaciers with the help of the gathered information. The study also aimed to make an in-depth comparison between the Veiki moraines located in northern Sweden and the Veiki moraines found within the study area in Tibet. The landforms were mapped using ArcMap and Google Earth Pro. The mapping revealed that the distribution of the glacial landforms was as expected in this area based on the background knowledge, and also suggested that glaciers have existed in this exact area for a very long time. The investigation of Veiki moraines proves that they can be found in an alpine glacial environment, which previously has not been shown. It also provides further support for the idea that Veiki moraines form on top of thick moraine complexes.